Implementasi Psikoedukasi Untuk Meningkatkan Penanaman Sikap Peduli Sosial Pada Siswa SMP Islam Sarbini Grabag - Purwati purwati; Muhammad Japar; Susmawati Surya Asih; Zulfa Zuyyina Rifki (Jurnal Pemberdayaan Masyarakat, 2022)
Social care is a person's empathetic attitude where one party can feel what is being experienced. The purpose of this service is psychoeducation as a method to broaden understanding in order to increase the cultivation of social care attitudes for students of Sarbini Grabag Islamic Junior High School. The methods applied in this activity are lectures, group discussions, games, and training. Implementation in this service activity includes the planning stage, the implementation stage, and the evaluation stage. The results of the service activities obtained are that students begin to understand the importance of instilling social care attitudes and can foster student awareness to increase empathy for others in the surrounding environment and students can apply it in everyday life.